An analysis of vehicular emissions at Kansas State University - Struck, Jessica Marie (Kansas State University, 2019)
There have been a wave of recent interest in understanding the dynamics of vehicular emissions in university towns. Using data from a recent survey of Kansas State University students, faculty, and staff-which includes a detailed itinerary of a day’s worth of travel -I assess spatial and temporal trends of emissions at Kansas State University. By combining the survey data with secondary sources of data, including vehicular emissions data from Fueleconony.gov and trip distance information from Google, I obtain improved measure for the quantity of emissions produced during each trip. After an extensive cleaning of the data, I develop heat maps for emissions composed of shape files identifying zip-code boundaries and a raster layer. I find that most vehicular emissions are concentrated around campus, with the highest level of emissions occurring during rush hour. Furthermore, faculty and staff appear to, on average, produce more emissions than students. I also investigate how proposed methods for reducing emissions will affect these spatio-temporal trends. Specifically, I show that walking or biking short distances instead of driving may lead to a small overall reduction in vehicular emissions.
Keywords: Emissions; Spatial-Temporal; Transportation